Serological studies of influenza infection among population in southern region of Kazakhstan during the 2018-2021 epidemic season - Shamenova, Mira Galautdinovna; Glebova, Tatyana Ivanovna; Klivleyeva, Nailya Galiveyevna; Baiseiit, Sagadat Bakhytkyzy; Baimukhametova, Asem Maratovna; Saktaganov, Nurbol Temirbayevich; Ongarbayeva, Nuray Syrlybayevna; Ismagulova , Dariya Azamatovna (Journal of the Pakistan Medical Association, 2023)
Objective: To conduct serological studies of influenza infection rate during an epidemic. Methods: The retrospective study was conducted at the Research and Production Centre for Microbiology and Virology, Almaty, Kazakhstan, and comprised data, including blood samples, from patients with symptoms of acute respiratory viral infection, bronchitis and pneumonia during 2018-21 from various healthcare institutions in the Almaty region. Serological tests on blood serums were carried out sing haem agglutination inhibition assay and enzyme-linked immunosorbent assay. Data was analysed using Graph Pad Prism 9. Results: Of the 779 blood samples, 392(50.3%) came from women and 387(49.7%) from men. The overall age range was 0-80 years. Serological analyses using haem agglutination inhibition assay showed the presence of anti-hemagglutinins against pandemic A(H1N1)pdm09 virus in 292(37.5%) samples, influenza A/H3N2 virus in 340(43.6%) and type B virus in 53(6.8%). Antibodies against two subtypes of influenza A virus and type B virus were simultaneously identified in 25(3.2%) cases, whereas against influenza A (H1N1+H3N2) viruses in 69(8.9%). In enzyme-linked immunosorbent assay, antibodies against influenza A/H1N1pdm virus were detected in 108(13.9%) cases, against A/H3N2 virus in 105(13.5%) and type B virus in 65(8.3%). Antibodies simultaneously against two subtypes of influenza A virus were identified in 46(5.9%) of blood serums, and against influenza A and B viruses in 60(7.7%). Conclusion: Co-circulation of influenza A and B viruses was observed, confirming the role of influenza viruses in the epidemic process. Key Words: Virus, Influenza, Antigen, Serum, Diagnosis.